Tyrosinase inhibitory activity of native plants from central Argentina: Isolation of an active principle from Lithrea molleoides - Chiari, Maria Eugenia (2010)
Screening of 91 native plants from central Argentina was carried out with the aim of finding new sources of anti-tyrosinase compounds. Extracts obtained from Achyrocline satureioides, Artemisia verlotiorum, Cotoneaster glaucophylla, Dalea elegans, Flourensia campestris, Jodina rhombifolia, Kageneckia lanceolata, Lepechinia floribunda, Lepechinia meyenii, Lithrea molleoides, Porlieria microphylla, Pterocaulon alopecuroides, Ruprechtia apetala, Senna aphylla, Sida rhombifolia, Solanum argentinum, Tagetes minuta and Thalictrum decipiens exhibited more than 90% inhibition of tyrosinase monophenolase activity at 1000 μg ml-1. D. elegans, L. meyenii and L. molleoides were the most potent with IC50 values of 0.48, 10.43 and 3.77 μg ml-1, respectively. D. elegans, L. molleoides and T. decipiens also showed more than 90% inhibition of diphenolase activity at 1000 μg ml-1, with the first of these being the most effective (IC50 = 49.27 μg ml-1). (Z,Z)-5-(trideca-4,7-dienyl)-resorcinol (1) was isolated from L. molleoides as an effective tyrosinase inhibitor with l-tyrosine or l-DOPA as substrates (IC50 = 0.49 and 14.94 μg ml-1, respectively). Compound 1 was 37 times more active in monophenolase inhibitory activity than kojic acid used as a reference. Effective extracts as well as (Z,Z)-5-(trideca-4,7-dienyl)-resorcinol could prove to be promising preservative agents for use in the food industry.